Dual-Contrast Cellular Magnetic Resonance Imaging - Rohan Dharmakumar; Zhouli Zhang; Ioannis Koktzoglou; Sotirios A. Tsaftaris; Debiao Li (Molecular Imaging)
Negative contrast magnetic resonance imaging (MRI) methods using magnetic susceptibility shifting agents have become one of the most important approaches in cellular imaging research. However, visualizing and tracking labeled cells on the basis of negative contrast is often met with limited specificity and sensitivity. Here we report on a MRI method for cellular imaging that generates a new contrast with a distinct topology for identifying labeled cells that has the potential to significantly improve both the sensitivity and the specificity. Specifically, we show that low flip-angle steady-state free precession MRI can be used to generate fast three-dimensional images of tissue that can be rapidly processed to generate quantitative metrics enabling color overlays indicative of regions containing labeled cells. The technique substantially improves the ability of MRI for detecting labeled cells by overcoming the fundamental limits that currently plague negative contrast methods.